How do Members of the European Parliament (MEPs) hold the European Central Bank (ECB) accountable? A descriptive quantitative analysis of three accountability forums (2014-2021) - Elsa Clara Massoc (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
The ECB is independent, but it is also accountable to the European parliament (EP). Yet, how the EP has held the ECB accountable has largely been overlooked. This paper starts addressing this gap by providing descriptive statistics of three accountability modalities. The paper highlights three findings. First, topics of accountability have changed. Climaterelated accountability has increased quickly and dramatically since 2017. Second, if the relationship between price stability and climate change remains an object of conflict among MEPs, a majority within the EP has emerged to put pressure for the ECB to take a more active stance against climate change, precisely on behalf of its price stability mandate. Third, MEPs engage with the climate topic in very specific ways. There is a gender divide between the climate and the price stability topics. Women engage more actively with climate-related topics. While the Greens heavily dominate the climate topic, parties from the Right dominate the topic of Price stability. Finally, MEPs adopt a more united strategy and a particularly low confrontational tone in their climate-related interventions.
Keywords: 330; accountability; European Central Bank; European Parliament; climate; price stability